2021
DOI: 10.1177/09754253211040206
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Disconnected: The Role of ICT in Women’s Livelihood Restoration in the Resettlement Site Kannagi Nagar in Chennai, India

Abstract: In Chennai, Development-Induced Displacement and Resettlement (DIDR) pushes the urban poor to resettlement sites in the outskirts of the city. One of those sites is Kannagi Nagar, located 15 km from the city centre, in which women suffer from more significant livelihood deprivation. As there is evidence of Information and Communication Technology (ICT) being useful in development, this study aims to explain the role of ICT in the livelihood restoration and enhancement of the social and financial capital for wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…This has resulted in their increased participation within organizations, augmented support from neighbors and the community at large, improved skill sets, superior employment opportunities and an escalation in income. However, it was observed that women generally have not yet harnessed the full potential of their mobile phones (Almira & Van Eerd, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in their increased participation within organizations, augmented support from neighbors and the community at large, improved skill sets, superior employment opportunities and an escalation in income. However, it was observed that women generally have not yet harnessed the full potential of their mobile phones (Almira & Van Eerd, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Women must turn to the informal economy as a means of survival. More importantly, a different study done in India (Almira & van Eerd, 2021) provides evidence of how urban slum redevelopment initiatives put women at risk for vulnerability and poverty.…”
Section: Urbanizationmentioning
confidence: 99%